VD_FINDINFO HC / 2013 / 391 vom 20. Juni 2013 - VD Tribunal cantonal (2013)
EXPULSION DE LOCATAIRE, DEMEURE, BAIL À LOYER, LOYER, EXIGIBILITÉ, RÉSILIATION, ANNULABILITÉ, EFFICACITÉ | 257d CO, 7 RULV, 257 CPC (CH)